1982
DOI: 10.1002/ijc.2910290417
|View full text |Cite
|
Sign up to set email alerts
|

Tumor enhancing T lymphocytes in mice: Further studies on characteristics and mechanism of activity

Abstract: In order to test the possibility that tumor-enhancing T lymphocytes can suppress other lymphoid cells, such as those with anti-tumor activity, their effect was tested in an allogeneic response of cell-mediated lysis. Normal thymocytes and spleen cells from mice with advanced tumors, two populations which enhance the growth of solid tumors, both suppressed the generation of CML. Since these results suggest that the mechanism of enhancement by T cells may resemble suppression in other immune responses, we looked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…The titration data suggest that perhaps any effective component of the immune reaction, such as macrophages, T cells, natural killer (NK) cells, or antibody and complement, may stimulate tumor if present in proper proportion (75)(76)(77). It seems convincing, judging from the titration of antibody, that one and the same molecular species can either facilitate or inhibit tumor growth depending only upon the concentration of that molecular species (78), although some species of splenic effector cells are apparently more stimulatory or inhibitory to tumor growth than are others (79,80). However, the observations with antibody do not encourage the belief that the immune response is divisible into stimulating and inhibiting compartments.…”
Section: Titrationsmentioning
confidence: 99%
“…The titration data suggest that perhaps any effective component of the immune reaction, such as macrophages, T cells, natural killer (NK) cells, or antibody and complement, may stimulate tumor if present in proper proportion (75)(76)(77). It seems convincing, judging from the titration of antibody, that one and the same molecular species can either facilitate or inhibit tumor growth depending only upon the concentration of that molecular species (78), although some species of splenic effector cells are apparently more stimulatory or inhibitory to tumor growth than are others (79,80). However, the observations with antibody do not encourage the belief that the immune response is divisible into stimulating and inhibiting compartments.…”
Section: Titrationsmentioning
confidence: 99%
“…These studies, carried out with thymus-defective animals (vs normal animals), have demonstrated a relationship between the appearance of a severe villus atrophy and a thymus-dependent host cell during a GVHR, and prompted the authors to postulate that the progression of an intestinal GVHR from the 'stimulatory' to the more destructive, 'acute' form of the disease is the result of a more severe (or longer-lasting) delayed-type hypersensitivity reaction. Whether the progressive atrophy of the thymus in LLca TB animals is related, via a premature release of immature thymocytes reactions (Small, 1977(Small, , 1978(Small, , 1982Treves et al, 1974), to the development of a PGI is presently being investigated. It should be noted, however, that the absence of MHC-restriction in PGI development, as demonstrated here, would suggest that lymphocyte involvement in the mechanism(s) leading to a PGI occurs through non-specific, MHC-independent cells or soluble factors.…”
Section: Discussionmentioning
confidence: 99%
“…This tumour-induced effect on the thymus has been explained by a premature migration of the immature Lyt 2-, L3T4-thymocytes (pre-T-cells) to the peripheral lymphoid organs (Small, 1977(Small, , 1982Small, Lasser-Weiss & Daniel, 1979). These immature thymocytes, expressing the T-cell receptor, are reportedly capable of serving as effector cells for tumour growth by non-specifically suppressing (or overriding) cell-mediated immune reactions including the cytotoxic T-cells directed against the tumour (Small, 1977(Small, , 1978(Small, , 1982Treves et al, 1974). Furthermore, these 'effector thymocytes' have previously been suggested to enhance a GVHR following allografts of spleen cells from LLca TBA and NTB mice (Paquette et al, 1981 ;Potworowski, Sikorska & Lemieax, 1982).…”
Section: Discussionmentioning
confidence: 99%